Impacts of pollution abatement projects on happiness: an exploratory study in China - Jin, Zhizhou; Zeng, Saixing; Cao, Cong; Ma, Hanyang; Sun, Daxin (2020)
Pollution has been a global concern in recent decades, promoting related actions in an increasing number of areas. While pollution can lead to unhappiness, will pollution abatement simply increase people's happiness? We analyze relevant happiness data collected before and after China's South-to-North Water Diversion Eastern Route Pollution Control Project to test this idea. The empirical results indicate that the pollution abatement project may not enhance happiness in its duration. Some residents may temporarily sacrifice something (such as employment or income), which offsets the positive effect of environmental improvement on their happiness. In subgroup analyses, rural people are found to benefit more from environmental improvement and suffer less in happiness compared with the urban, and so are low-income people compared with the high-income ones. The findings offer new insights into the costs of pollution in terms of happiness and highlight the need to abate pollution meticulously. © 2020 Elsevier Ltd